EFFECT OF SOME CHEMICAL AND PHYSICAL FACTORS ON THECOCCI SHAPE FORMATION OF HELICOBACTER PYLORIISOLATED FROM PATIENTS WITH DUODENUM ULCER - Radif, Hala; Saleh, Dhuha (Iraqi Journal of Science, 2024)
Helicobacter pylori was islotaed localy from patients with Duodenal Ulcer. Twobiopsies were taken from each patient, the first used for isolation of H. pylori usingski row medium, the second used for rapid urease test. Optimum growth temperaturewas 37 c. Isolated H. pylori was identified according to bacterial shape, graw stain,biochemical test, sensitivity to cephalothin & resistance to nalidixic acid. The resultshowed that component of culture media, light, & oxygen are important factors affecting Hansformed from spiral to coccoid shapes. It has been noticed that usingBrain – heart infusion a gar and blood a gar base with growth supplement give &5%blood, percentage transformation to coccoid shape was less than using the sameculture media without blood and growth supplements. Results indicated thatavoiding exposure of culture media to light and oxygen (more than 5%) maintainspiral shape of H. pylori for 20 – 30 days when stored at 4 c taking in considerationa pH of (6.9 – 8).